A serosurvey study of hand, foot and mouth disease in healthy children aged 6 to 71 months old in West Bandung and Bandung Region, Indonesia - Rodman Tarigan Girsang; Kusnandi Rusmil; Eddy Fadlyana; Budi Setiabudiawan; Riyadi Adrizain; Rizky Perdana Mulyadi; Arief Budiman; Rona Kania Utami; Behesti Zahra Mardiah; Muhammad Gilang Dwi Putra; Frizka Primadewi Fulendry; Dinda Tiaraningrum Nashsyah; et al. (BMC Infectious Diseases)
Abstract Background Hand, foot, and mouth disease (HFMD) is an infectious disease that often affects children under 5 years of age. Over the past 20 years, enterovirus 71 (EV71) has become a major concern among children, especially in the Asia-Pacific region. Currently, there are no data showing the seroprevalence of HMFDs in Indonesia. This study aimed to determine the seroprevalence of antibodies to EV71 infection in rural and urban areas. Methods This study was an observational analysis and cross-sectional seroprevalence survey of HFMD in children aged 6 to 71 months. The sampling locations were the Padalarang health centre, which is rural, and the Garuda health centre, which is urban. The total sample included 600 children aged 6–71 months from these two locations. Blood sample testing uses enzyme-linked immunosorbent assays (ELISAs) to identify subjects who are positive for IgG EV71 and the risk factors that may influence it. Results In total, 596 subjects (99.3%) were positive for the seroprevalence of EV71 IgG in rural and urban areas. Child age, sex, nutritional status, height/age, immunisation status, parental income, and father’s and mother’s educations were not statistically related in rural and urban areas (p > 0.05) because the rate of IgG EV71 seropositivity was very high. Conclusion This study revealed that the rate of IgG EV71 HFMD seropositivity in Indonesia, especially in the Padalarang health centre and Garuda health centre, was very high. Further research is needed to investigate HFMD cases because of the lack of attention given to this disease and the need to consider whether immunisation is necessary to prevent HFMD. Trial registration This study is registered at clinicaltrials.gov, National Clinical Trial (NCT) No. NCT05637229.